Analysis of The Essential Oil from Lantana camara Leaves and Its Cytotoxic Potential Against T-47D Breast Cancer Cells - Suryati Suryati; Enda Desriansyah Aziz; Mai Efdi; Fatma Sri Wahyuni; Dira Hefni (Jurnal Riset Kimia, 2021)
Lantana camara Linn is a family of Verbenaceae which grows wild and is widespread in various both tropical and sub-tropical countries. Isolation essential oil of the L. camara leaves extracted by hydrodistillation and were analyzed by Gas Chromatography-Mass Spectrometry (GC-MS). The results of GC-MS analysis show isocaryophyllene (14.39%), Ï-cymene (8.17 %), Î²-cubebene (7.8 %), Î±-pinene (7.64 %), and Î²-elemene (5.51 %) as the main compound. The cytotoxic activity of the isolated essential oil was highly toxic both to Artemia salina shrimp larvae (LC50 15.92 Âµg/mL) and to breast cancer cells T-47D (IC50 10.67 ÂµM).